2014
DOI: 10.4103/0259-1162.128898
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of premixed versus sequential administration of clonidine as an adjuvant to hyperbaric bupivacaine intrathecally in cesarean section

Abstract: Background:Density of the drugs injected intrathecally is an important factor that influences spread in the cerebrospinal fluid. Mixing adjuvants with local anesthetics (LA) alters their density and hence their spread compared to when given sequentially in seperate syringes.Aims:To evaluate the efficacy of intrathecal administration of hyperbaric bupivacaine (HB) and clonidine as a mixture and sequentially in terms of block characteristics, hemodynamics, neonatal outcome, and postoperative pain.Setting and Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Besides fentanyl, other drugs like clonidine and dexmedetomidine have also been studied in many trials to see the quality of spinal anaesthesia with hyperbaric bupivacaine in premixed and separate syringe sequential administration technique and found that separate administration of adjuvants with bupivacaine have beter haemodynamic and analgesic outcome 6,14 which is similar to our study.…”
Section: Discussionsupporting
confidence: 88%
“…Besides fentanyl, other drugs like clonidine and dexmedetomidine have also been studied in many trials to see the quality of spinal anaesthesia with hyperbaric bupivacaine in premixed and separate syringe sequential administration technique and found that separate administration of adjuvants with bupivacaine have beter haemodynamic and analgesic outcome 6,14 which is similar to our study.…”
Section: Discussionsupporting
confidence: 88%
“…This may be due to the change in the concentration and/or the chemistry of local anesthetics. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored intrathecal nonopioids as novel alternatives, such as α 2 -adrenergic receptor agonists [ 21 ] and neostigmine [ 22 ]. Dexmedetomidine is a highly selective α 2 -adrenergic receptor agonist that has sedative, analgesic, anxiolytic, sympatholytic, amnestic, anti-shivering, and opioid-sparing effects [ 23 ].…”
Section: Discussionmentioning
confidence: 99%